Perlindungan Hukum Atas Kreditur Yang Menggunakan Jaminan Personal - Hendra Yakub; Fauzie Yusuf Hasibuan; Udin Narsudin (Postgraduate of Jayabaya University, 2018)
Personal guarantees embodied in the agreement do not stipulate special conditions that require the guarantor to submit something tangible which will make it easier for the creditor to take action if the debtor defaults and guarantor breaks promises, this is what makes the underwriting agreement less meaningful or meaningful in its function as collateral which is manifested in a separate deed, individual guarantee seems to be only a moral obligation. The method used in this research is normative juridical research, the data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. For data analysis, it was done by using qualitative juridical analysis method. The research results show that, it is still difficult to ask for the credit agreement arrangement and the provisions in the clause or individual guarantee conditions that can provide legal protection for creditors. In the implementation of billing bad credit through personal guarantees through the court by executing confiscation of guarantees against the assets of the personal guarantor, the results have not been optimal, because the personal guarantee agreement does not include information on the assets of the insurer and clauses that are compelling or binding on the assets of the insurer, so that in practice the court will have difficulty executing the property of the personal guarantor.